Do Labmates Matter? The Relative Importance of Workplace Climate and Work-Life Satisfaction in Women Scientists’ Job Satisfaction (International Journal of Gender, Science and Technology, 2015)
Workplace climate and work-life balance are two factors that influence women’s decisions to leave or remain in a science workplace. &This study applies structural equation modeling to data from nearly 600 early-career geoscientists to examine relationships among perceptions of workplace climate, work-life satisfaction, job satisfaction and productivity. &The results include analytic path models comparing women to men, women professionals to women graduate students, and women professionals with child caregiving responsibilities to those without. &For all groups, workplace climate–measured in terms of both collegial interactions in the workplace and influence on decision-making–outweighed satisfaction with work-life balance in shaping job satisfaction, which in turn positively influences perceived productivity. &Work-life balance increased in importance and became significantly more influential for women caregivers. &The findings suggest that institutional efforts to improve workplace climate benefit all academics, while unmitigated work-life conflict may tip the balance for women’s satisfaction. & &